DEVELOPMENT AND ASSESSMENT OF ADENIUM OBESUM FLOWER EXTRACT-BASED OINTMENT FOR ANTIFUNGAL ACTIVITY - Manisha Singh; Neha Singhb
This study has been carried out on the formulation development and evaluation of ointment of flower extract of Adenium obesum for its anti-fungal activity. The extraction was done using ethyl alcohol. Six different ointment formulations were prepared and assessed for physical appearance, drug contents, viscosity, pH, spreadability, stability, drug release and in vitro drug diffusion. All formulations showed excellent stability as their drug contents (96.26 - 97.31 %), viscosity (524.25 - 529.23 cP), pH (6.2 - 6.6), spreadability (12 - 14) and in vitro drug diffusion (82.34 - 84.84 %) were found within the range. In long term stability study, it was found that the formulations F3, F4, F5 & F6 were most prominent formulations. The antifungal activity of formulations was found to be in a dose dependent manner. Therefore, we concluded that the formulation might be utilized in the management of fungal infections i.e., dermatitis, pruritis, etc.